ANALISIS KEPENTINGAN - KINERJA ATRIBUT DESTINASI WISATA PANTAI MUTUN DI PROVINSI LAMPUNG - Novintara, Ismi Aztri Vicia; Hudoyo, Agus; Sulaiman, Achdiansyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
Mutun Beach is one of the many tourist destinations in Lampung Province. In order for this tourist destination to be able to compete with other tourist destinations, Mutun Beach needs to show the performance of its tourism attributes. The main objective of this study was to analyze the tourism attributes that need to be maintained and improved their performance in Mutun Beach. This research was conducted for four weeks in August and September 2020. Samples were taken in stages from the Mutun Beach’s visitors. Each week, interviews were conducted three to four times, namely on one working day and two days on weekends. Prior to the interview, the samples were randomly selected. The number of samples was 40 respondents. The main data collected were the importance and performance scores of the 17 tourism attributes. Data were analyzed using Importance Performance Analysis (IPA). The results showed that of the 17 attributes studied, there were 11 attributes had to be maintained, namely the number of parking lots, lodgings, communication skills of officers, ability of officers to provide information, courtesy and friendliness of officers, service speed of officers, willingness of officers to help tourists, security and convenience of traveling, as well as the officer’s understanding and sensitivity to the needs of tourists. The results showed that there are four attributes that need to be improved, namely cleanliness of toilets, trash bins, worship facilities and cleanliness of beach areas. Key words: attributes, importance, performance.